2005
DOI: 10.1029/2004gc000786
|View full text |Cite
|
Sign up to set email alerts
|

NAO signature in a Bermuda coral Sr/Ca record

Abstract: [1] We present a 55-year-long record of Sr/Ca in a Bermuda coral (Diploria strigosa), which we use to reconstruct local twentieth century climate features. The clearest climate signal emerges for the late-year Sr/Ca. Although the coral was collected in shallow water (12 m), the correlation with station data is highest for temperatures at 50 m depth (r = À0.70), suggesting that local temperatures at the collection site are not representative for the sea surface temperatures in the adjacent open ocean. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 46 publications
(64 reference statements)
3
31
0
Order By: Relevance
“…5). Additional evidence in support of this hypothesis is provided by coral cores from Bermuda that exhibit thicker layers of CaCO 3 deposition, and therefore greater rates of calcification, corresponding to years of negative SST anomalies (indicative of deeper MLD) (31,32), negative winter NAO events (33), and presumably higher offshore productivity (25,26).…”
Section: Resultsmentioning
confidence: 92%
“…5). Additional evidence in support of this hypothesis is provided by coral cores from Bermuda that exhibit thicker layers of CaCO 3 deposition, and therefore greater rates of calcification, corresponding to years of negative SST anomalies (indicative of deeper MLD) (31,32), negative winter NAO events (33), and presumably higher offshore productivity (25,26).…”
Section: Resultsmentioning
confidence: 92%
“…1), than do corals from North Rock 17,18 . Differences between the north and south have been found in sea surface temperature (SST) records generated from coral Sr/Ca that are attributed to differences in coastal circulation 19 . Studies from the north reef have found agreement between seasonal variations in coral Sr/Ca and SST data from Hydrostation S; however, there is no relationship between North Rock Sr/Ca and SST at interannual timescales (that is, comparing data for wintertime only) 19,20 .…”
Section: Carbon Isotope Records From Bermudamentioning
confidence: 99%
“…Differences between the north and south have been found in sea surface temperature (SST) records generated from coral Sr/Ca that are attributed to differences in coastal circulation 19 . Studies from the north reef have found agreement between seasonal variations in coral Sr/Ca and SST data from Hydrostation S; however, there is no relationship between North Rock Sr/Ca and SST at interannual timescales (that is, comparing data for wintertime only) 19,20 . This indicates that the Sr/Ca to SST correlation is driven by the seasonal cycle that occurs each year in both records rather than the North Rock Sr/Ca accurately capturing interannual ocean conditions in the southern and central Sargasso Sea.…”
Section: Carbon Isotope Records From Bermudamentioning
confidence: 99%
“…Bermuda, a northernmost location for surface coral growth and near a site of high, deep sea sedimentation rates, has been the location for several reconstructions of past climate from coral [Draschba et al, 2000;Druffel, 1997;Kuhnert et al, 2005], foraminifera and alkenone based proxy reconstructions .…”
Section: Study Sitementioning
confidence: 99%